Pengaruh Permainan Mengubur Angka terhadap Kemampuan Mengenal Angka di Pendidikan Anak Usia Dini Maghfirah Kota Padang - Anisa, Elva; Jaya, Indra; Yeni, Indra (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This study aims to determine the influence of the game burying numbers to know ability to recognize the number of child. The research method used is quantitative in the form of experimental quasy.Theresults showed that the childre’s in the experimental class used the game to bury numbers had a higher average compared to the control class that used number card games. The average number of the experimental class is 91.87 and the average number of the control class is 82.5. Based on the data analysis that has been done that thitung>ttabel,is 2.9281> 2, 10092. There for can be concluded that game burying numbers to know ability to recognize number of child.